The Duty of a Christian People under Divine Visitations - Smart, Newton, 1798?-1879 (Salt Lake City, UT : Project Gutenberg, 2015)
"The Duty of a Christian People under Divine Visitations" by Newton Smart is a theological treatise written in the early 19th century. The work primarily addresses the responsibilities of Christians during times of divine judgment and crisis, urging collective and individual repentance and reform. It reflects on the moral and spiritual obligations of the faithful in the face of national calamities, such as plagues or wars, and calls for deep introspection and reformation. The opening of the book sets a somber tone, discussing the state of anxiety and fear prevalent in the nation due to impending judgment from God, as indicated by a spreading pestilence. Smart stresses the importance of turning back to God through prayer, humility, and repentance, quoting scripture to emphasize his points. He asks what course a Christian society should adopt in such dire times, pushing for a united response of faith and supplication while reflecting on the failures that have led to this state of divine displeasure. As the dialogue progresses, it becomes clear that the author intends to embolden his readers to pursue both personal and national reform grounded in Christian doctrine and practice. (This is an automatically generated summary.)
Release date is 2015-06-03
Transcribed from the 1832 J. G. & F. Rivington edition by David Price
Keywords: Providence and government of God